Determinants of Manufacturing Concentration Patterns in Mercosur - Iulia Traistaru; Christian Volpe Martincus (European Regional Science Association (ERSA), 2003)
Over the last fifteen years, Argentina, Brazil, Paraguay and Uruguay have implemented major economic reforms including unilateral trade liberalization programs and the constitution of a regional trade bloc, Mercosur. This trade policy change has led to a reallocation of resources across sectors and space. The impact of the trade liberalization on industrial production structures in Mercosur countries has been little investigated so far. How concentrated /dispersed are manufacturing activities' Have patterns of manufacturing concentration changed? What are the determinants of manufacturing concentration patterns' This paper identifies and explains relative concentration patterns of manufacturing activities in three Mercosur member countries, namely, Argentina, Brazil, and Uruguay, over the period 1970-1998. In particular, using econometric techniques, we analyse inter-industry and across-time differences in manufacturing concentration patterns and explain their main determinants over this period. Our research results suggest that some industries, such as Beverages, Tobacco and Leather are highly concentrated in relative terms, while industries such as Glass, Textiles, and Fabricated metal products are dispersed. We find that on average, relative manufacturing concentration has increased over the above mentioned period. While industries, such as, Non-electrical machinery, Electrical machinery and Professional and scientific instruments have experienced significant monotonic increases, other industries, such as Printing and publishing, Rubber products, and Non-ferrous metals have registered a reversal of their relative concentration levels. Our econometric analysis indicates that localization of demand and comparative advantage factors are the main driving forces of the observed relative manufacturing concentration patterns.
Keywords: 330